Peran Work Engagement Dalam Menurunkan Turnover Intention Perawat: A Systematic Review - Nisa Dewanti; Kusnanto Kusnanto; Slamet Riyadi Yuwono (FORIKES, 2021)
Background: Employees who are engaged will feel satisfied with their work so they feel very involved in their work, and this has a positive effect on improving physical and mental health, improving performance, and reducing the level of absenteeism and turnover intention on employees. Objective: To find out how the role of work engagement is to reduce nurse turnover intention. Method: This systematic review was based on Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA). The database used in this studied was Scopus, ScienceDirect, Emerald, PubMed, and Semanticscholars were limited to publications from 2015 to 2020, full-text article and in english. The keywords used were